2013
DOI: 10.3198/jpr2013.02.0007crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘CP 05‐1526’ Sugarcane

Abstract: ‘CP 05‐1526’ (Reg. No. CV‐155, PI 667554) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugar Cane League, Inc., and released to growers for organic (muck) and sand soils in Florida in October 2012. CP 05‐1526 was selected from the cross CP 98‐1029 × CP 88‐1162 made at Canal Point, FL in December 2002. The female parent (CP 98‐1029) is a sugarcane cultivar released for commercial use in Florida in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Multiple approaches have been and are being used for eliminating rust negative effect on yield of sugarcane. These include disease monitoring, adjustment of management practices, fungicide applications (Raid et al, 2011) and development of new cultivars with resistance to orange rust by intensive screening in the breeding program (Zhao et al, 2013). The increase in frequent applications of fungicides results in high input cost and low net profits of sugarcane production (Jiang, 1985;Staier et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple approaches have been and are being used for eliminating rust negative effect on yield of sugarcane. These include disease monitoring, adjustment of management practices, fungicide applications (Raid et al, 2011) and development of new cultivars with resistance to orange rust by intensive screening in the breeding program (Zhao et al, 2013). The increase in frequent applications of fungicides results in high input cost and low net profits of sugarcane production (Jiang, 1985;Staier et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The CP program consists of six stages, namely Crossing, Seedling, and Stages I, II, III, and IV (Zhao et al, 2012a). The tonnage depends on the number of stalks per unit area and mean stalk weight at harvest time (Zhao et al, 2013). Cane tonnage and sucrose content are the two primary components of sucrose yield in sugarcane.…”
Section: Researchmentioning
confidence: 99%
“…For instance, the cross (family) X09-1236 in 2012 had the lowest mean brown rust rating among 295 families, but Bru1 was not detected in its parents CP03-1160 and CP04-1105 (Table 4). These results suggested that other genes may also be involved in the either durable or non-durable resistance of sugarcane plants to brown rust in addition to Bru1 [23] as reported by other studies [32][33][34][35]. Racedo et al [34] recently found that the predominant source of resistance to brown rust in the sugarcane breeding program at Tucuman, Argentina would be a resistance source independent of the Bru1 gene.…”
Section: Bru1 In Parental Clones and Rust Rating In Their Progenymentioning
confidence: 62%
“…Multiple approaches have been and are being used for eliminating the negative effects of brown and orange rusts on yields, quality, and profits of sugarcane. These include standard breeding, molecular marker assisted selection, disease monitoring, adjustment of management practices, fungicide applications, and selection of rust resistant cultivars in the breed program by intensive rust screening [23]. Studies have shown that parents producing progeny with a high frequency of transgressive segregates for agronomic traits should provide the best opportunity for sugarcane breeders to select clones superior to their parents [36].…”
Section: Relationships Between Brown and Orange Rustsmentioning
confidence: 99%
See 1 more Smart Citation